2008
DOI: 10.1002/jpln.200625217
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions and dynamics of soil nitrogen under 15N‐labeled cow urine and dung patches on a sandy grassland soil

Abstract: Grazing animals highly influence the nutrient cycle by a direct return of 80% of the consumed N in form of dung and urine. In the autumn‐winter period, N uptake by the sward is low and rates of seepage water in sandy soils are high, hence high mineral‐N contents in soil and in seepage water as well as large losses of N2O are expected after cattle grazing in autumn. The objective of this study was the quanitfication of N loss deriving from urine and dung leaching and by N2O emission. Therefore the deposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 40 publications
5
33
0
1
Order By: Relevance
“…The overall values calculated are in line with literature values on N inputs with excreta (e.g. Virkajärvi et al 2010;Wachendorf et al 2008). The balances for areas Table 2 Nitrogen soil surface balances for the whole plot (plot balance) or for areas affected by dung (dung pats), urine (urine patches), grazing without N input through the animals (grazed areas) or the total area not affected by dung pats (urine ?…”
Section: Balance Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The overall values calculated are in line with literature values on N inputs with excreta (e.g. Virkajärvi et al 2010;Wachendorf et al 2008). The balances for areas Table 2 Nitrogen soil surface balances for the whole plot (plot balance) or for areas affected by dung (dung pats), urine (urine patches), grazing without N input through the animals (grazed areas) or the total area not affected by dung pats (urine ?…”
Section: Balance Resultssupporting
confidence: 82%
“…This might have been related to small overall N losses and small differences between N balances. Although N losses per dung and especially urine patch can be substantial (Wachendorf et al 2005(Wachendorf et al , 2008Yamulki et al 2000), losses integrated over the plot area would still be expected to be small as 92 to 97% of the plot areas had negative N balances (grazed areas, Table 2). Here, the N cycle would be relatively tight with active pools in soil and vegetation of similar sizes and a limited potential for fractionations (Robinson 2001).…”
Section: Balance Resultsmentioning
confidence: 99%
“…During grazing, vegetation-fixed carbon (C) and herbage nitrogen (N) is removed from a large area of pasture and much of it (75-90 % ingested N) is returned as high-concentration, excretal patches (Afzal and Adams 1992). Growing evidence suggests that the excreta from large herbivores may promote field-scale N losses via leaching or gaseous N emissions (Yamulki et al 1998;Hutchings et al 2007;Wachendorf et al 2008). To date, however, mechanistic understanding of grassland responses to animal excreta is limited, and accurate accounting of urine and dung in models of grassland function remains a challenge (Hutchings et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no significant differences between urine and urine + various of microbial activity by urine as well as the denitrification of indigenous soil N pool (Lambie et al, 2012). In fact, Wachendorf et al (2008) found that 75% of urine-induced N 2 O emission originated from the indigenous soil mineral N pool in a German soil. In the case of fertiliser treatments, there was a clear N 2 O peak observed only in the CAN treatment (Figure 2c).…”
Section: Discussionmentioning
confidence: 83%